Pemanfaatan Limbah Sabut Kelapa (Cocopeat) dan Sekam Sebagai Media Tanam Budidaya Jamur Tiram (Pleurotus Ostreastus) - R, Risaldi; S, Subariyanto; M, Muhlis (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This study aims to determine the comparison of coconut fiber waste (Cocopeat) and rice husks with sawdust on the growth rate of oyster mushroom mycelium (Pleurotus Ostreatus). The type of research used is quasi-experimental research or pseudo-experiment with a Completely Randomized Design (CRD) model with 3 repetitions. This study uses the ANOVA test, then continued with the Duncan test if the treatment has an effect. The treatment given to the planting media per baglog is 700 grams of coconut fiber powder (Cocopeat), 420 ml of water, 80 grams of agricultural lime. 700 grams of rice husks, 420 ml of water, 80 grams of agricultural lime. And 700 grams of sawdust planting media, 420 ml of water, 80 grams of agricultural lime. In the control treatment with sawdust planting media, treatment A with coconut fiber waste planting media (Cocopeat), and treatment B with rice husk planting media. The parameters tested in this study were survival, growth in length of oyster mushroom mycelium (Pleurotus Ostreatus), and environmental factors. The results of the study on survival showed that there were no contaminated baglogs such as yellow spots, green spots, and rotten baglogs. And the results of the growth of mycelium length, treatment A was the best treatment, namely treatment with coconut fiber waste planting media (Cocopeat). Treatment A had the highest average mycelium length of 8.7 cm. While in environmental factors, the results of observations on the temperature of the mushroom house were obtained in the range of 25 °C-30 °C.